Menakar Etika Komunikasi Digital di Tengah Maraknya Disinformasi E-Commerce - Mely Eka Karina; Rasianna Br. Saragih; Rifa’i (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
The development of e-commerce in Indonesia has changed the communication pattern of digital marketing, but on the other hand poses a serious challenge in the form of increasing disinformation that threatens communication ethics and consumer trust. This study aims to analyze how digital communication practices in e-commerce violate the principles of communication ethics and its impact on consumer trust, focusing on the phenomenon of fake reviews, hidden endorsements, and excessive product claims. The method used was descriptive qualitative by collecting data through in-depth interviews with business actors, influencers, and active consumers, as well as digital observation of promotional content on Tokopedia, Shopee, and TikTok Shop. Data analysis uses the Miles & Huberman model with triangulation validation of theories, sources, and methods. The results show that e-commerce disinformation reflects a crisis of digital communication ethics, where economic persuasion takes precedence over honesty and transparency. Based on the theory of the Elaboration Likelihood Model (ELM), consumers are more easily influenced by peripheral paths such as high ratings and influencer imagery without critical evaluation. This condition lowers public trust and strengthens the need for the implementation of digital communication ethics, increasing people's digital literacy, and strict regulation of misleading communication practices.